IMPLEMENTASI KNOWLEDGE MANAGEMENT MODEL SECI PADA INDUSTRI KREATIF SKALA RUMAH TANGGA - Siswanto, Heri (Magister Manajement Studies Program, 2025)
This article is entitled Implementation of SECI's Knowledge Management Model in Household Scale Creative Industries. This research is motivated by the problem of mastering the knowledge of craft workers faced by SMEs. Where one step of the solution is to apply Knowledge Management. Nonaka and Takeuchi's knowledge model is a spiral knowledge model known as the SECI model – Socialization, Externalization, Combination, and Internalization. The focus of this knowledge model emphasizes knowledge transfer, learning transfer, and innovation. The purpose of this research is to describe and analyze: (1) the Implementation of the SECI Knowledge Management Model in Creative Industries on a Household Scale; (2) Obstacles to the Implementation of the SECI Knowledge Management Model in Creative Industries at a Household Scale; (3) Solutions for overcoming obstacles in the Implementation of the SECI Knowledge Management Model in Household Scale Creative Industries. The research method used in this research is descriptive with a qualitative approach. Data collection techniques were carried out using interviews, observation, and documentation. Technical analysis of data is done by descriptive narrative. Based on the information obtained from the informants and the results of data processing, the results were found that: (1) The socialization carried out included weekly routine discussions, barriers to lack of mastery of knowledge, the solution was training and brainstorming; (2) Externalization is proven by the presence of meeting minutes, the obstacle is that there is no guidebook, the solution is to make a pocketbook; (3) The combination can be seen from the activity of categorizing various handicraft products, barriers to the availability of technology, solutions by procuring production machines and the internet; (4) Internalization can be seen in the existence of product data, barriers that have not been integrated, solutions by implementing knowledge repository as an integrated database collector.